Protecting the Internet Without Wrecking It: The root of this problem is software controlled by its developer. - Stallman, Richard (Boston Review)
In this article the author cites the fundamental issue pertaining to Internet security as being computer software that is controlled by its developers, which are usually large corporations. The author states that the solution to this is more freedom for users to have access to open source software options, where users and change aspects of the software they don't like. The author proposes ending the patenting of software as one solution.